2020
DOI: 10.20546/ijcrbp.2020.710.002
|View full text |Cite
|
Sign up to set email alerts
|

Response of three tossa jute (Corchorus olitorius L.) cultivars produced in Benin to salinity stress at germination and young plant stages

Abstract: The response of three tossa jute cultivars Ordinaire, 5-Doigts and Acc : Sud 2 to salt stress was evaluated at germination and young plant stages. Five NaCl concentrations: 0; 30; 60; 90 and 120 mM NaCl were used. Seeds were submitted to NaCl in petri dishes and germination was checked every day during thirty days in a completely randomized design with four replicates. Four-week old plants were submitted in pots to the same five NaCl concentrations by irrigation every two days for two weeks in screen house. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Thus, salinity effect on African basil plant growth depends on the growth parameter taken into account. This result corroborated those reported in other vegetable species including sweet basil [21,19,24,22,31]. According to the results, root fresh mass followed by shoot fresh mass appeared to be the most salt sensitive parameters in basil and could be validly used to characterize the response of other African basil cultivars to salinity.…”
Section: Leaves Rootssupporting
confidence: 89%
“…Thus, salinity effect on African basil plant growth depends on the growth parameter taken into account. This result corroborated those reported in other vegetable species including sweet basil [21,19,24,22,31]. According to the results, root fresh mass followed by shoot fresh mass appeared to be the most salt sensitive parameters in basil and could be validly used to characterize the response of other African basil cultivars to salinity.…”
Section: Leaves Rootssupporting
confidence: 89%
“…In Benin, tossa jute (Corchorus olitorius L.), commonly called "crincrin" occupies an important place in the diet of the population and is one of the most widely practiced market garden crops (Savi, 2009). In our previous study, we have reported that NaCl salt stress reduced tossa jute plants growth and that the response varied greatly according to the cultivar (Loko et al, 2020). To mitigate the negative effects of salinity on plants and circumvent this stress, one of the techniques consists of adding macro elements such as potassium, calcium, magnesium or phosphorus to enrich the substrate used for growing plants.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as the major abiotic factor that limits plant productivity and agricultural yield [1,2]. Several studies have reported that salts present in soil and in irrigation water reduce plant growth [3][4][5][6][7][8][9][10] and consequently reduce crop production. Soil salinity affects plant growth, either through osmotic effects or ionic toxicity effects.…”
Section: Introductionmentioning
confidence: 99%